2005
DOI: 10.1261/rna.7272305
|View full text |Cite
|
Sign up to set email alerts
|

The contributions of dsRNA structure to Dicer specificity and efficiency

Abstract: Dicer processes long double-stranded RNA (dsRNA) and pre-microRNAs to generate the functional intermediates (short interfering RNAs and microRNAs) of the RNA interference pathway. Here we identify features of RNA structure that affect Dicer specificity and efficiency. The data presented show that various attributes of the 3 end structure, including overhang length and sequence composition, play a primary role in determining the position of Dicer cleavage in both dsRNA and unimolecular, short hairpin RNA (shRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
199
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(224 citation statements)
references
References 27 publications
19
199
0
3
Order By: Relevance
“…Our 39-RACE analyses revealed that both RNAi vectors generate at least four siRNA species that were common between the vectors. These findings are consistent with a previous report that demonstrated flexibility (i.e., base-pair shifting) in dsRNA cleavage by Dicer (Vermeulen et al 2005). Notably, the most prevalent species generated by the RNAi vectors was shared, representing z50% of the 39-RACE sequences analyzed (n = 10-12 per vector per strand).…”
Section: Shrna Expression and Potency Is Overhang Dependentsupporting
confidence: 92%
See 2 more Smart Citations
“…Our 39-RACE analyses revealed that both RNAi vectors generate at least four siRNA species that were common between the vectors. These findings are consistent with a previous report that demonstrated flexibility (i.e., base-pair shifting) in dsRNA cleavage by Dicer (Vermeulen et al 2005). Notably, the most prevalent species generated by the RNAi vectors was shared, representing z50% of the 39-RACE sequences analyzed (n = 10-12 per vector per strand).…”
Section: Shrna Expression and Potency Is Overhang Dependentsupporting
confidence: 92%
“…These shRNAs were designed to have minimized 39 overhangs (2-4 U's resulting from Pol-III termination; Ng et al 1979;Ohshima et al 1981;Kunkel et al 1986) to resemble the 2-nt 39 overhangs that result from Drosha cleavage. Overhangs of this length provide optimal substrates for Exportin-5 and Dicer (Zeng and Cullen 2004;Vermeulen et al 2005). In addition, target sequences were selected to account for the +1-G nucleotide of the mouse U6 promoter and to contain AU-rich 39 ends, both of which promote loading of the antisense strand (Khvorova et al 2003;Schwarz et al 2003).…”
Section: Shrna Expression and Potency Is Overhang Dependentmentioning
confidence: 99%
See 1 more Smart Citation
“…In Arabidopsis, 21-nt sRNAs are produced by DCL4, 24-nt sRNAs by DCL 2 or DCL 3, and DCL1 produces miRNAs that are 22 nucleotides in length [27,40]. In this study a large percentage of the sRNAs had read lengths of 20-24 nucleotides, which is typical for DICER-processed sRNA products [24][25][26].…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, most of these enzymes conduct activity by forming an intramolecular pseudodimer between two tandem RNase III domains [25]. In these cases, RNA recognition is accomplished primarily through a PAZ domain that binds the 3′ end of the pre-miRNA [26-28] with a preference for 2 nt overhangs [29], though other parts of the molecule-including the C-terminal dsRBD and platform-also contribute to substrate recognition. Ultimately, Dicers couple the functionality of their RNase III domains to distal RNA recognition domains like PAZ.…”
mentioning
confidence: 99%